Analisis Faktor Penyebab Kelambatan Penyaluran Dana Desa: Studi Kasus di Kecamatan Membalong Kabupaten Belitung - Sri Suryanovi (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2019)
The realization of Village Fund distribution from the State Treasury Account to the Regional Public Account (RKUD) and from the RKUD to the Village Cash Account in 2017 and 2018, generally is slowness, so the realization of Village Fund absorption and output achievements not on targeted. This study aims to knowing causative factors the slowness, especially in the villages in Kecamatan Membalong Kabupaten Belitung, so that it is entitled